Tracing the Melanesian Person: Emotions and Relationships in Lihir - R Hemer, Susan (University of Adelaide Press, 2013)
Through this engaging ethnographic account of connections, conflicts and loss in Lihir, Hemerâ s own fieldwork journey of making relationships, experiencing disputes and finally leaving the field, is mirrored. Structured into three parts, the book works through the complexities of creating and sustaining relationships, the evaluation of conduct as moral and the practices of conflict, and the experiences and transformations of death and grief. Throughout these parts various emotions are highlighted and interrogated for their relationship to psychological understandings and definitions: love, anger, jealousy, sadness. Emotions are also understood in a historical context and as connected to social changes wrought by interactions with global phenomena such as religion.